Design and control of a STATCOM based on hybrid cascaded H‐bridge and full‐bridge neutral point clamped multilevel inverter. Issue 17 (22nd January 2021) - Miremad, Armin; Khalaj Monfared, Kourosh; Iman‐Eini, Hossein; Neyshabouri, Yousef
Abstract : This study presents a STATic synchronous COMpensator (STATCOM) based on hybrid cascaded H‐bridge and full‐bridge neutral point clamped (HC‐FNPC) inverter. The advantages of HC‐FNPC over symmetric and asymmetric cascaded H‐bridge (HB) in STATCOM application are verified in terms of number of power components and voltage balancing capability. A control strategy is proposed to achieve control aims, i.e. reactive current compensation and balancing the voltages of capacitors. HC‐FNPC‐based STATCOM consists of two types of cells, i.e. full‐bridge neutral point clamped (FNPC) and HB cells with one and two capacitors in their DC side, respectively. A hierarchical balancing scheme is proposed to regulate the voltage of capacitors in mixed cells. In the first control layer, the voltage vector of cells is adjusted so that the active power is uniformly distributed among the cells. In the second control layer, the switching redundancies of FNPC are used to provide voltage balancing. The introduced balancing scheme not only provides voltage balance among capacitors, but also distributes the reactive power equally among the cells and increases the reliability in this way. The performance of the proposed control is validated through simulation in MATLAB/SIMULINK environment and experimental results based on a single‐phase nine‐level HC‐FNPC‐based STATCOM laboratory prototype.